Food reserves, hunger and food market stability as correlates of infant, child, and maternal mortality in Nigeria - Nnadi, Elizabeth Ifeyinwa; Ezenwaka, Chinonye Oluchi; Nnadi, Kenneth Ugwu (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
This article investigates the interplay between food reserves, hunger levels, food market stability, and their impact on infant, child, and maternal mortality rates in Nigeria. Based on historical data of a 22-year time series, the study employs regression analysis to explore these correlations, providing empirical insights crucial for public health and policy formulation. The findings reveal significant relationships between the mortality rates and the economic indicators studied. Specifically, the regression outputs indicate that for infant mortality rate (INMR), there is an inverse association with the overall consumer price index (CPIA), implying that as CPIA increases, INMR decreases. Conversely, the food consumer price index (CPIF) shows a positive correlation with INMR, suggesting that higher food prices may lead to increased infant mortality. Moreover, hunger (HUNG) exhibits a negative coefficient with INMR, indicating that higher levels of hunger are associated with higher infant mortality rates. For maternal mortality rate (MAMR), the regression results indicate a positive relationship with CPIA and CPIF, implying that both overall and food-specific inflation may contribute to higher maternal mortality rates. Additionally, hunger shows a significant negative impact on MAMR, suggesting that addressing hunger could potentially reduce maternal mortality rates in Nigeria. Similarly, the analysis for under-five mortality rate (U5MR) reveals negative coefficients for CPIA and HUNG, indicating that higher overall inflation and hunger are associated with increased child mortality rates. Conversely, CPIF exhibits a positive coefficient with U5MR, suggesting that higher food prices may also contribute to higher child mortality rates. These findings underscore the complex dynamics between economic factors, food security, and mortality outcomes in Nigeria. They form the bases for recommendations highlighting the urgent need for targeted policies that address food accessibility, market stability, and hunger to mitigate adverse public health outcomes among vulnerable populations, particularly infants, children, and mothers.